PERKEMBANGAN TEKNOLOGI DAN SISTEM INFORMASI UNTUK PENINGKATAN E-GOVERNMENT DALAM PELAYANAN PUBLIK - Suprihatmi Sri Wardiningsih (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
Abstract Growth of information technology in this case computer technology can support the decision making in conducive modern organizations of work in organization can be finished quickly, accurate, and efficient. Information technology (TI) defined by as technology used to obtain get the, manipulation, presenting data. The All manager is this time claimed by their ability to be able to exploit the information influencing organizations so that can make decision precisely pursuant to the information. At our tataran governance recognize the term e-government which is becoming trend in this time, How exploiting TI in governance which we recognize with the phenomenon " e-government"nya ? The reality exploiting TI in governance do not such as those which we conceive the, congeniality TI in governance still limited to computer for the typing of and support the process of eye administration. Function TI for the process of data processing and transaction which ready complex and also public information a long way off from expectation. Keywords: Information Technology, e-government, public service.